STUDY ON CALCINATION OF HALLOYSITE NANOTUBE (HNT)TO ENHANCE EFFICIENCY OF 2-MERCAPTOBENZOXAZOLE (MBO) LOADED CALCINED HNT EPOXY AS A SMART ANTICORROSIVE COATING FOR CARBON STEEL - HARIS, MUHAMMAD (2020)
Various approaches have been adopted in oil and gas industry for the mitigation of corrosion, of which protective coatings were one of the most effective.